The Nrf2 Activator CDDO-Imidazole Suppresses Inflammation-Induced Red Blood Cell Alloimmunization - Che-Yu Chang; Rosario Hernández-Armengol; Kausik Paul; June Young Lee; Karina Nance; Tomohiro Shibata; Peibin Yue; Christian Stehlik; David R. Gibb (Antioxidants)
Experimental Objective: During red blood cell (RBC) transfusion, inflammation promotes the production of anti-RBC alloantibodies that can cause significant hemolytic events. Avoiding RBC antigen exposure is the only strategy to prevent RBC alloimmunization in transfusion recipients. Identifying mechanisms that inhibit alloimmunization may lead to novel prophylactic interventions. One potential regulatory mechanism is the activation of the transcription factor nuclear factor erythroid-derived 2-like 2 (Nrf2), a master regulator of antioxidant pathways. Pharmacologic Nrf2 activators induce antioxidant production and improve the sequelae of inflammatory diseases. Thus, we tested the hypothesis that a Nrf2 activator, 1-[2-cyano-3-,12-dioxooleana-1,9(11)-dien-28-oyl]-imidazole (CDDO-Im), regulates inflammation-induced RBC alloimmunization. Methods: WT and Nrf2-deficient mice were treated with inflammatory stimuli and CDDO-Im prior to transfusion with RBCs expressing the KEL antigen (KEL+ RBCs). Anti-KEL IgM and IgG were measured in the serum of transfused mice. Nrf2-activated gene expression and interferon activity were measured in mice and human macrophages pre-treated with CDDO-Im and interferon stimuli. Results: Here, we report that CDDO-Im induces Nrf2-activated gene expression and inhibits type 1 interferon activity, which promotes RBC alloimmunization in transfusion models. In mice transfused with KEL+ RBCs, pre-treatment with CDDO-Im inhibited inflammation-induced anti-KEL antibody production and increased the post-transfusion recovery of KEL+ RBCs in a Nrf2-dependent manner. CDDO-Im also inhibited RBC alloimmunization in mice with pre-existing inflammation. Conclusions: These results indicate that the activation of the Nrf2 antioxidant pathway regulates RBC alloimmunization to the KEL antigen in a pre-clinical model. If these findings translate to other models and human studies, Nrf2 activators may represent a potential prophylactic intervention to inhibit alloimmunization.